Do Infants in the Neonatal Intensive Care Unit Diagnosed with Urinary Tract Infection Need a Routine Voiding Cystourethrogram? - Flannery, Dustin D (J Matern Fetal Neonatal Med, 2017)
OBJECTIVE: To determine if infants diagnosed with urinary tract infection (UTI) in the neonatal intensive care unit (NICU) require a routine voiding cystourethrogram (VCUG). STUDY DESIGN: Retrospective data analysis from three centers for infants admitted to the NICU born between 2000 and 2013 and diagnosed with UTI. RESULTS: 126 infants from three centers were diagnosed with UTI during their hospitalization. Renal ultrasound (RUS) was performed in 115 infants (91.2%), of which 69 (60%) were abnormal. Mild to moderate hydronephrosis or pelviectasis were the most common abnormalities identified (n=34, 30%). There were 14 infants (12%) with severe abnormalities on RUS. VCUG was performed in 71 infants (56%), of which 3 (4%) were interpreted as abnormal with grade 2 vesicoureteral reflux (VUR) or less (2 infants normal RUS and 1 infant abnormal RUS). CONCLUSION: More than 50% of infants with a UTI had an abnormal RUS but severe abnormalities were found only in 11% of infants. Only 4% of infants with UTI had VUR; none of these infants had severe VUR on VCUG. A routine VCUG after UTI in the NICU has a low yield and may be reserved for infants with severe or persistent abnormalities on RUS.